The Religious Spirit Embedded in The Work Ethic of Female Workers at PT. Rokok Djarum Kudus - Jufri, Masudi; Muflihah, Muflihah; Masuwd, Mowafg (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
The phenomenon of workers in factories has become a real reality. Women as a living entity have become part of the family's economic life, but the spirit of work for women is part of religious expression. Work ethic, religion and regulations are part of the life of women factory workers in Kudus. This research aimed to observe the religious spirit embedded inside work ethic of female workers at PT. Rokok Djarum Kudus and the relationship of work ethic with religious fanatics that are part of women's lives. According to Sjafri Sairin's economic exchange and Mudrajad Kuntjoro's work ethic theories by qualitative analysis cross collected data by interviews, observations with purposive sampling, and documentation are the main parts of the study’s exploration. The research findings show that the very strict regulations from the company do not make them give up on their work but remain enthusiastic about building a productive work ethic. The work ethic of these female workers is evident in their daily factory work and their religious practices, both at work and at home. These female workers are able to provide a decent living for their families and the companies they work for.